The Law of Lawmaking as Quasi Constitutional Legislation: Undang-Undang Pembentukan PeraturanPerundang-Undangan Sebagai LegislasiKuasi Konstitusional - Hadyan Iman Prasetya (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
Constitutional Court Decision No. 91/PUU-XVIII/2020 regarding the judicial review of the Job Creation Act, marked for the first time Court decide prevailed on behalf of petitioners in a procedural judicial review case. The Decision erects a legal discourse relating to the superiority of the Lawmaking Act against other statutes, in terms of its position as a ground for conducting a procedural judicial review. It departs from the common understanding that all statutes are equal, no one statute could be superior to others. Normatively researched while laboring statutory, conceptual, and comparative approaches, the study resulting two answers. First, the superiority of the Lawmaking Act would be best described by quasi constitutional legislation theory. Second, the majority opinions in recent Constitutional Court Decisions reflected the entrenchment of the Lawmaking Act, which fit the quasi constitutional legislation theory